Should bank capital requirements be less risk-sensitive because of credit constraints? - Gene Ambrocio; Esa Jokivuolle (Bank of Finland, 2017)
We consider optimal capital requirements for banks' lending activities when the potential trade-off between financial stability and economic (productivity) growth is taken into account. Both sides of the trade-off are affected by banks' credit allocation, which in turn is affected by the risk weights used to set capital requirements on bank loans. We find that when firms are credit constrained, the optimal risk weights are flatter than those that are only set to safeguard against bank failures and their social costs. This provides an additional rationale for capital requirements to be less 'risk-sensitive'. Differences in company productivity have a further effect on the profile of optimal risk weights, and may amplify the 'flattening' effect.
URN:NBN:fi:bof-201705151298
Keywords: E44; G21; G28; 330